Medindo o impacto social da regeneração urbana pela cultura : percepções dos moradores da Mouraria - Proença, Inês Vasconcelos (2015)
This research focus on the capacity of cultural investment, in the context of urban regeneration, to accomplish the rhetorical of social revitalization and the extent to which it offers socially sustainable solutions to local community. To that purpose, the work is directed towards the meanings and practices of Culture-led Urban Regeneration (CLUR) in the inner-city and it is suggested measuring its impact on subjective social dimensions over residents. One of the study’s main concerns is the degree to which CLUR might really address the expectations that policy makers have as an integrated and sustainable 'tool' to approach declined urban areas. To realize these goals, the Lisbon neighbourhood of Mouraria will be used as a case study and as a means of testing our research hypothesis. Measuring the subjective social impacts of urban regeneration in the neighbourhood, from the residents perspective, becomes the study’s central focus. And, equally relevant, there was a concern of improving measuring instruments capable of assessing the subjective social impact of culture-led urban regeneration projects. This dissertation refers to the European and Portuguese experiences, looking to draft these policies genealogy, to discuss the rhetoric behind and to uncloak how residents of declined areas perceive such change in their place.